1991
DOI: 10.1021/jm00115a014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure-activity relationships of a novel series of non-peptide angiotensin II receptor binding inhibitors specific for the AT2 subtype

Abstract: Structure-activity relationships are reported for a novel class of 4,5,6,7-tetrahydro-1H-imidazo[4,5-c]pyridine-6-carboxylic acid derivatives that displace 125I-labeled angiotensin II from a specific subset of angiotensin II (Ang II) binding sites in rat adrenal preparations. This binding site is not the Ang II receptor mediating vascular contraction or aldosterone release, but, rather, is one whose function has not yet been fully elucidated. It has been identified in a number of tissues and has a similar affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
1
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 6 publications
5
117
1
3
Order By: Relevance
“…As in murine myotubes, Ang II directly induced protein degradation in soleus muscle, as determined by tyrosine release, and was more effective at lower concentrations than in murine myotubes. To confirm that the effect was direct and to determine the receptor involved, the protein degradation assay was performed in the presence of ZD7155, a selective competitive antagonist for the Ang II type 1 (AT 1 ) receptor (Junggren et al, 1996) or PD123319, a selective AT 2 receptor antagonist (Blankley et al, 1991), or saralasin, a competitive nonselective Ang II antagonist (Steinhausen et al, 1986). The results in Figure 7A show attenuation of the increased protein degradation by both PD123319 and saralasin, while ZD7155 had no effect.…”
Section: Resultsmentioning
confidence: 98%
“…As in murine myotubes, Ang II directly induced protein degradation in soleus muscle, as determined by tyrosine release, and was more effective at lower concentrations than in murine myotubes. To confirm that the effect was direct and to determine the receptor involved, the protein degradation assay was performed in the presence of ZD7155, a selective competitive antagonist for the Ang II type 1 (AT 1 ) receptor (Junggren et al, 1996) or PD123319, a selective AT 2 receptor antagonist (Blankley et al, 1991), or saralasin, a competitive nonselective Ang II antagonist (Steinhausen et al, 1986). The results in Figure 7A show attenuation of the increased protein degradation by both PD123319 and saralasin, while ZD7155 had no effect.…”
Section: Resultsmentioning
confidence: 98%
“…Cardiovascular responses to microinjections of ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) into the ARCN. The ARCN (ϳ2 mm long in the rostrocaudal direction) was arbitrarily divided into the following three equal segments (the coordinates mentioned for each segment indicate the level caudal to the bregma): the rostral segment (2.1-2.9 mm), middle segment (2.9 -3.7 mm), and caudal segment (3.7-4.5 mm).…”
Section: Resultsmentioning
confidence: 99%
“…High concentrations of ANG-(1-12) have been reported in the rat brain, and cells immunoreactive for ANG-(1-12) have been identified in the nucleus tractus solitarius (NTS) of the rat (1,30). Bilateral microinjections of ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) into the NTS have been reported to elicit transient depressor responses and an attenuation of baroreflex sensitivity (1). Chronic immunoneutralization of endogenous brain ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) by intracerebroventricular injections of anti-ANG-(1-12) IgG in hypertensive rats have been reported to elicit antihypertensive effects (21).…”
mentioning
confidence: 99%
“…1) suggested that the AT2R plays an important role in the regulation of satellite cell differentiation and muscle regeneration. To investigate the role of the AT2R during muscle regeneration in vivo, we infused mice with the AT2R antagonist PD123319 (28) in a setting of CTX-induced injury ( Fig. 2A).…”
Section: At2r Expression Increases During Muscle Regeneration-mentioning
confidence: 99%